Diltiazem versus metoprolol for rate control in atrial fibrillation with rapid ventricular response in the emergency department. (15th December 2016) - Hines, Michelle C.; Reed, Brent N.; Ivaturi, Vijay; Bontempo, Laura J.; Bond, Michael C.; Hayes, Bryan D.
Abstract: Purpose: The impact of patient-specific factors on the choice of β-blocker versus calcium channel blocker therapy for rate control in emergency department (ED) patients treated for atrial fibrillation (AF) was investigated. Methods: A retrospective cohort study was conducted to evaluate the influence of demographics, prior medication use, hemodynamic and clinical characteristics, and other variables on selection of first-line therapy for AF among patients admitted to the ED of an academic medical center over a 22-month period (October 2012–July 2014) who received i.v. treatment with either the β-blocker metoprolol (n = 45) or the calcium channel blocker diltiazem ( n = 55) for rate control. Results: Significant predictors of the selection of metoprolol versus diltiazem included a past history of AF (odds ratio [OR], 8.3; 95% confidence interval [CI], 1.396–72.713; p = 0.032) or diabetes mellitus (OR, 7.2; 95% CI, 1.208–58.490; p = 0.042) and being prescribed a β-blocker prior to presentation (OR, 27.8; 95% CI, 4.704–272.894; p = 0.001); a history of calcium channel blocker use prior to ED presentation was a negative predictor of β-blocker use for initial rate control (OR, 0.1; 95% CI, 0.005–0.265; p = 0.002). No differences in the effectiveness or safety of diltiazem and metoprolol were identified. Indicators of hemodynamic and clinical response to ED management were not predictive of discharge medication selection. Conclusion: The drug class used for rate control prior to ED admission was the most significant predictor of medication selection for rate control in the ED setting.